(untitled) (Research, Society and Development, 2021)
This article aimed to discover dreams and expectations in the process of building identities for the adult life of adolescents, students of a Rural Family House, Bom Jesus das Selvas (CFR/BJS), in the State of Maranhão, Northeastern Brazil. The target population consisted of 30 young people (collecting narratives in semi-structured interviews), the Casa’s technical team and the researchers adopted the action research approach. The data obtained were examined using the thematic analysis approach, based on two axes: Learning to dream within the CFR and Learning to live outside the CFR. It was possible to conclude that the methodology of popular education for citizenship, respecting the local culture, developed by the partner NGO, with the goal of creating a Center of Excellence in Education for Young People in the Country, generated an experience of innovation and social transformation for development sustainable community. It managed to overcome the fragmentation of content existing in rural practice and articulate education with the lives of students, their desires and future perspectives, establishing goals for water, food and income self-sufficiency.